Volume element model mesh generation strategy and its application in ship thermal analysis. (December 2015) - Yang, S.; Dilay, E.; Ordonez, J.C.; Vargas, J.V.C.; Chalfant, J.
Highlights: We present a hexahedral mesh generation strategy for the volume element model. The proposed mesh generation strategy is applied in ship thermal analysis. Highly accurate representations of the ship geometry can be achieved. Plausible ship thermal solutions are obtained using a coarse independent mesh. The strategy enhances the overall computational efficiency of the VEM. Abstract: This paper introduces a mesh generation strategy devised and implemented for the volume element model (VEM), and elaborates key contributions of the strategy in enhancing the VEM as a prominent tool in ship thermal modeling and simulation. The VEM mesh generation strategy employs ray crossings and ray– triangle intersection algorithms developed in previous studies, and constructs sufficiently accurate geometric representations of the whole ship within permissible time frame using hexahedral meshes. In addition, this work demonstrates the strategy's practicality in thermal analysis of a notional all-electric ship, which is characterized by intricate structures and multiple internal components, i.e., thermal loads. Ship thermal solutions obtained in this assessment verify the proposed mesh generation strategy's ability to improve the overall computational efficiency of the VEM, by allowing it to obtain plausible thermal solutions with respect to time and space using a coarse independent mesh.